COVID-19's Impact on the Indian Tourism and Hospitality Industry - Dr. Chitrranjan Singh (International Journal of Engineering and Management Research, 2021)
The COVID-19 pandemic is the world's most serious human calamity in 2020, and it has wreaked havoc on India's economy. The COVID-19 pandemic has wreaked havoc on India's economy in a variety of ways. The impact of COVID-19 on one of the most vital sectors, tourism, has been exceedingly distressing and has resulted in significant losses. As a developing economy, India was already in a precarious position before COVID-19. India's sudden nationwide lockdown was the world's largest. The four stages of continuous countrywide lockdown, which lasted more than two months, had a tremendous impact on India's tourism economy. The Indian travel and tourism sector contributed 6.8% of India's GDP in 2019 and generated 39,821 million jobs, or about 8.0 percent of total employment. The Indian tourism and hospitality industry is now forecasting a job loss of 38 million people. The Indian government has taken significant steps to resurrect the tourism industry. The Indian travel and tourist industry has begun to set general safety and hygienic standards for hosting and serving clients, as well as attempting to restore people's faith in travelling again following the corona outbreak.